Study on effect of offset defect on mechanical property of honeycomb structures. (December 2021) - Xu, Ping; Xiao, Xianliang; Yao, Shuguang; Kong, Lingxiang
Abstract: Honeycomb is widely used because of its excellent energy absorption characteristics during compression. However, offset defects in the manufacturing process are inevitable and affect the energy absorption characteristics. In order to study the effect of offset defect, the finite element model was established firstly. The verified finite element model was used to simulate the honeycomb structure under different offsets. The simulation shows that with the increase of the offset λ, the deformation mode of the honeycomb can be divided into three stages and the platform strength increased first and then decreased, and the decrease was obviously greater than the increase. Then the theoretical calculation formula of platform strength of the honeycomb under offset defect was obtained by simple folding theory. The results show that for commonly used honeycomb specifications, when λ  = 0.4, the platform strength increases the most, which is 7.99%, and when λ  = 1.0, the platform strength decreases the most, which is 18.03%. The theoretical results are similar to the simulation results. For Y-shaped element, the errors are 2.13% and 2.04% at λ  = 0.4 and 1.0 respectively, for whole honeycomb, the errors are 0.29% and 4.82% at λ  = 0.4 and 1.0 respectively. Therefore, the platform strength of honeycomb can be improved by increasing the offset appropriately.